Himba: infâncias, violências e resistências em “Se o passado não tivesse asas”, de Pepetela - Lima, Maria Jéssica Sousa (2023)
Se o Passado não Tivesse Asas, a novel written by Pepetela and published in 2016, depicts two pivotal sociopolitical and historical periods in Angola: the conflicts for political control following the war for independence in the past, and a more contemporary phase characterized by economic growth and development. In this regard, this work seeks to analyze the interplay between literature, representations, and identities, emphasizing the role of the child character and the myriad forms of violence exacerbated by the backdrop of two wars. It attempted to approach the child as an active agent, delving into a theoretical exploration of childhood throughout modern history. The utilization of child characters in Pepetela´s literary oeuvre and those present in the works of other African writers is employed as a foundational source while contextualizing childhood in Angola. Interest further extends to comprehending the impact of context-induced violence on the characters, notably the protagonist, as well as the exploration and manifestation of remnants of colonial and sexual violence within the narrative. Lastly, an overview is presented regarding how the character Himba grapples with memories and forgetfulness, employing concepts such as territoriality, deterritorialization, and identity. All the factors under scrutiny align with our belief that literary representations of experiences offer a significant platform for articulating and examining individual and collective experiences ingrained in the unique social memory of the Angolan nation. To achieve these objectives, the works of authors such as Spivak (2010), Mata (1995, 2010, and 2022), Mbembe (2018), Fanon (1968), and others will be used.